Characteristics and Health Service Use of a Longitudinal Cohort of Carers Aged over 45 in Central and Eastern Sydney, Australia. - Harris-Roxas, Ben; Kabir, Alamgir; Kearns, Rachael; Webster, Gurdive; Woodland, Lisa; Barr, Margo (Health & Social Care in the Community, 2023)
Carers are a large portion of the Australian community. In 2018, 2.65 million Australians identified as carers, and almost one-third (32.6%) of this group were primary carers. There is currently a lack of understanding of the impact of being a carer on a person's health and wellbeing compared to non-carers. This research was undertaken to understand the health status, health risks, and health outcomes for carers in Central and Eastern Sydney, Australia (CES), who are 45 years of age or over. A record linkage study using data from the 45 and Up Study, Medicare Benefit Scheme claims, hospitalisations, and deaths was undertaken on participants in CES (n = 29,489). Characteristics of carers were described and outcomes over an eight-year period were also calculated. Around 12% of the cohort was carers at a given time, though most transitioned in and out of caring roles over a five-year period. Compared with non-carers, carers in CES had higher rates of self-reported smoking, anxiety, psychological distress, heart disease, and self-rated poor quality of life. Carers had higher rates of general practitioner use than non-carers (Adj. HR (95% CI): 1.21 (1.13, 1.30)). However, hospital admissions and mortality were not significantly different. This study confirms that a small proportion of carers remain in carer roles for many years. Caring often starts suddenly, and people need to quickly adapt to their new role. The finding that carers are well-engaged with GPs suggests they may play an important role in identifying carers who are struggling, and delivering interventions for carers.